Apnéia obstrutiva do sono pós- menopausa: contribuições da fonoaudiologia - Matos, Jessica Santos de (2022)
Obstructive sleep apnea syndrome (OSAS) is the result of recurrent obstruction, lasting ten seconds or more, of the upper airways during sleep. The main risk factors for this condition are: advanced age, sex, body fat, hormones, genetic and anatomical factors. The contributions of Speech-Language Pathology and Audiology are extremely important in the diagnosis, treatment and rehabilitation of the syndrome. This study aimed to list the contributions of Speech Therapy in the treatment of OSAS in women who have entered menopause. This is an integrative literature review and included a selection of articles published in the last 10 years available in the Latin American and Caribbean Literature on Health Sciences (LILACS), Google Scholar and Scientific Electronic Library Online (SCIELO) databases. ). The descriptors obstructive sleep apnea syndrome, OSAS, menopause and Speech-Language Pathology and Audiology were used in the design of the searches. The Boolean phrase and was also used in the crossing of the descriptors aiming at a better identification of the articles of interest. After applying the inclusion and exclusion criteria, ten articles were chosen to extract the results that obtained 3 categories of interest: 1. Symptomatology associated with obstructive sleep apnea syndrome; 2. Predisposing factors for obstructive sleep apnea syndrome; 3. Contributions of speech therapy in the treatment of obstructive sleep apnea syndrome. The role of speech therapy proved to be positive as a complementary therapy in the treatment of OSAS. However, the importance of a multidisciplinary team in the prevention, diagnosis and treatment of OSAS cases must be considered.